A Review on Benign Prostatic Hyperplasia (World Journal of Current Medical and Pharmaceutical Research, 2019)
Benign prostatic hyperplasia is the enlargement of prostate gland mainly seen in men aged above 50 years. It has been observed that 8 out of 10 men having prostate enlargement. It is mainly caused due to over growth of benign glandular tissue and leads to the constriction of urethra and decreased urine output. Diagnosis for BPH involves Obligatory and optional evaluation. The main risk factor for BPH is age.BPH is clinically manifested as obstructive LUTS (lower urinary tract symptoms) and irritable LUTS (lower urinary tract symptoms).Treatment for BPH depends on number of factors like age, prostate size, and severity of symptoms . Alpha1Adrenergic receptor antagonist decreased lower urinary symptoms and increased flow rates of urine in men with symptomatic BPH but do not reduce the long term risk of urinary retention. 5 alpha reductase inhibitors decrease the production of dihydrotestosterone with in the prostate which results in decreased prostate volume, increased peak urinary flow rate, improvement of symptoms, and decreased risk of acute urinary retention. Combination therapy involves 5 alpha reductase inhibitors and alpha adrenergic blockers it is effective in patients having LUTS with prostatic enlargement. Anticholinergics and phosphodiesterase inhibitors were also used in the management of BPH. Medication therapy is used in all the three stages but it only delays surgery in patients with severe BPH.